PENGARUH KEMAMPUAN, DISIPLIN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN REJOSO KABUPATEN NGANJUK - DYAN ARINTOWATI (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2016)
Complaints and grievances of public services to the public service so that raises people's perceptions of how the performance of the employees of the District in serving the community public services. This study aims to prove the effect of partial and simultaneous variable abilities, discipline and employee satisfaction to employee performance at the District Office Rejoso Nganjuk. The method used in this sampling is sampling saturated or census, the number of samples is equal to the total population of the census called by employees at the district office Rejoso Nganjuk totaling 44 people. Analysis of multiple linear regression equation used to determine the effect of several independent variables on the dependent variable. The results of this study suggest that the ability, discipline and employee satisfaction partially affect the performance of employees at the District Office Rejoso Nganjuk. This is evidenced by the acquisition t each variable is greater than t table and the significance value less than the limit of significance 5%. The ability, discipline and employee satisfaction simultaneously affect the performance of employees at the District Office Rejoso Nganjuk. This is evidenced by the acquisition of F count each variable larger than F table and the significance value less than the limit of significance of 5%. Job satisfaction which has dominant influence on employee performance at the District Office Rejoso Nganjuk when compared with the ability and discipline of employees working at the District Office Rejoso Nganjuk. This is evidenced by the large value of the regression of job satisfaction.